Solid‐Phase Synthesis of Peptidols via Reductive Cleavage Through a Benzotriazole Linker - Chen, Szu‐Hsuan; Chuang, Hui‐Ying; Rajavel, Chitra; Kai Lin, Yi; Chang, Shu‐Han; Tsai, Pei‐Chen; Chen, Hui‐Ting; Sun, Chung‐Ming; Selvaraj, Anand; Kao, Chai‐Lin (Advanced synthesis & catalysis, 2024)
Peptidols were prepared through the reductive cleavage of benzotriazole intermediates obtained from the on‐bead activation of 3,4‐diaminobenzoyl linkers. Remarkably, this method used commercially available amino acid residues and resins without further modification. Pure peptidols were collected with only filtration in 49%–87% yield. Only the derivatives with aspartic acid as the first C‐terminal residue required sophisticated chromatography purification. Esters and carboxylic acids were identified as side products and were suppressed by additional reduction or reduction in DMF. Remarkably, the reduction of peptides with the first aspartic acid residue at the C‐terminal afforded a C‐terminal lactone, which could be reduced by deprotection at 0 °C. For the synthesis of branched peptidols, the bulky wedge structures of the branched peptides resulted in low total yields, which were improved to 23%–28% by using peripheral Boc groups and SPPS on the Tental gel resin. In addition, this method gave two peptaibols, SPF‐5506‐A4 and Ac‐Gramicidin A, in 11% and 46% yields, respectively.